Effectiveness of reminiscence therapy on health related quality of life among the old age people residing at a selected old age home, Bengaluru, India - Shah, Lata Kusum; Rashmi, Serah; Nanjundappa, Dhanpal (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: The well being of oneself, happiness with one’s situation in life and ability to perform and control the different situation of life is HRQoL. Reminiscence therapy is a way for residents of assistant living facilities to become better acquainted with one another and strengthen the personal value and self esteem. The objective of this study was to assess the HRQoL while application of Reminiscence Therapy among the old age people who are residing at a selected old age home in Bengaluru, India. Materials and Methods: For this study quasi experimental research design was selected and convenient sampling technique was used to collect data from 60 samples staying at old age home by using the SF-36 scale. The samples in experimental group receive 10 sessions of reminiscence therapy each session last for 45 minutes to 1 hour. The experimental group was divided into 6 groups each group having five members for group discussion related to the topics like childhood memories, education pattern, first job and first salary, marriage, first child etc. Post test data was collected after a week of implementation of Reminiscence Therapy. Then the data was analyzed and interpreted. Results: The findings of the study with regard to pretest HRQoL reveals that 86.7% has poor HRQoL, 13.3 % moderate HRQoL and no one was having good HRQoL in experimental group. In control group 56.7% has poor HRQoL, 43.3% moderate HRQoL and no one was having good HRQoL. But in posttest, only in experimental group there was significant improvement in HRQoL as 83.3% has good HRQoL, 13.3% moderate HRQoL and 3% poor HRQoL. Conclusion: This study concluded that with significant improvement in the SF-36 Scale score after administration of the reminiscence therapy and seen improvement in HRQoL.